2010
DOI: 10.1073/pnas.1007407107
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic and evolutionary implications of a diverse paleobiota in amber from the early Eocene of India

Abstract: For nearly 100 million years, the India subcontinent drifted from Gondwana until its collision with Asia some 50 Ma, during which time the landmass presumably evolved a highly endemic biota. Recent excavations of rich outcrops of 50–52-million-year-old amber with diverse inclusions from the Cambay Shale of Gujarat, western India address this issue. Cambay amber occurs in lignitic and muddy sediments concentrated by near-shore chenier systems; its chemistry and the anatomy of associated fossil wood indicates a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(183 citation statements)
references
References 48 publications
4
179
0
Order By: Relevance
“…The abundance of invertebrates preserved in amber from the Caribbean and other geographical regions has led to macroevolutionary and macroecological insights about some groups (28)(29)(30), but such approaches have not previously been possible for vertebrates. The Caribbean island Anolis lizards have contributed to our understanding of evolutionary processes as a well-known case of adaptive radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of invertebrates preserved in amber from the Caribbean and other geographical regions has led to macroevolutionary and macroecological insights about some groups (28)(29)(30), but such approaches have not previously been possible for vertebrates. The Caribbean island Anolis lizards have contributed to our understanding of evolutionary processes as a well-known case of adaptive radiation.…”
Section: Resultsmentioning
confidence: 99%
“…They come mainly from small, thin lenses of carbonaceous shale, representing nearshore continental sediments, that occur 1-3 m above the lower of two major lignites (Lignite 2) present at Vastan and Mangrol mines 17,18,29,30 . The vertebrates are closely associated with plant fossils and amber indicating that they lived in or near a coastal tropical rainforest dominated by Dipterocarpaceae 31 . Three dinoflagellate species from the zone producing the vertebrates imply an age not older than 55 Myr; one species from about 12 m higher than the vertebrates has been interpreted as 'basal Ypresian, B54 Myr' 26 .…”
mentioning
confidence: 99%
“…The formation of Indian amber took place probably during Eocene period i.e. 53 million years ago [10]. Fossils records show that Coniferopsida such as Walkomiella, Searsolia and Paranocladus resin producing trees were once part of lower Gondwana [11].…”
Section: A Possible Origin Of Amber In Tropical Beach Sandmentioning
confidence: 99%
“…The present studies showed that dimensions of Indian AMF ranged from 40-70μm and density per kilogram of sampled sand could be from 200-300 indicating their relative rarity. Larger pieces of fossiliferous amber need to be ground, polished and chemically treated [15,16,10], whereas, AMF as isolated in this work being small and thin can be easily processed, mounted in large number on a SM and could be studied using image analysis software. This work showed Keri, Arambol, Mandrem, Morjim, chapora, Baga, Miramar beach sand as most promising for retrieval of AMF possibly due to influence of turbulent currents of Tiracol estuary, Chapora river, Baga creek, and Mandovi river which could transport amber from unidentified hinterland terrestrial sources towards the sea.…”
Section: IIImentioning
confidence: 99%
See 1 more Smart Citation